PRINSIP NON-REFOULEMENT DALAMPERLINDUNGAN PENGUNGSI DI INDONESIA(BERDASARKAN KASUS PENGUNGSI ETNISROHINGYA DI INDONESIA KARENA KONFLIKRASIAL DI MYANMAR: Principles of non-refoulement in the Protection of Refugees in Indonesia (Based on the Case of Refugees of Rohingya Ethnic in Indonesia Due To Racial Conflict in Myanmar) - Wawo, Arnoldus Jansen Julian; Justinar, Jun (Faculty of Law, Universitas Trisakti, 2024)
Rohingya refugees need humanitarian assistance and have the right to protection from arbitrary return to places where they are at risk of torture. This rule is known as the principle of non-refoulement, which is understood as the basis for international protection for refugees. This thesis results from normative legal research using primary, secondary and tertiary legal materials. Data collection was carried out through literature study and interviews. The issues discussed are: how the principle of non-refoulementis regulated in national law in Indonesia, what is Indonesia's attitude in dealing with Rohingya refugees who have come to seek refugee in Indonesia, and why the principle of non-refoulement is still weak in its implementation in Indonesia. The results of this thesis research show that the principle of non- refoulement is regulated in Indonesia through Constituion of the Republic of Indonesia 1945 Article 28G, Act No.1 1979,Act No.5 1998, Act No.29 1999, Act No.37 1999, Act No.6 2011, People'sConsultative Assembly Decision No.17 1998, President Ordinance No.125 2016, Directorate General of Imigration Ordinance No.IMI-1489 2010, Government Ordinance No.31 2013. Even though Indonesia'sfirm stance was demonstrated by not ratifying the Convention on the Status of Refugees, Indonesia still adheres to the principle of non-refoulement. The implementation of the non-refoulement principle inIndonesia is still weak because Indonesia itself has not ratified the 1951 Refugee Convention and the 1967 Additional Protocol.